Dampak Leverage, Kepemilikan Institusional dan Ukuran Perusahaan terhadap Kinerja Perusahaan pada Perusahaan Manufaktur Periode 2011-2015 - Deni Wardani; Maria Yeschrina Rudolfus (Jurnal Keuangan dan Perbankan, 2016)
The purpose of this research is to examine the effect of leverage, institutional ownership and firm size on firm performance in manufacture companies listed on the stock exchanges in Indonesia during 2011-2015. Puposive sampling is chosen as the sampling method of this study. Data obtained from secondary data in the annual reports of 71 companies listed on the Stock Exchange in 2011-2015. The result prove that firm size variable have negative significant effect with firm performance in manufacture companies. But, leverage and institutional ownership variable have not significant effect with firm performance in manufacture companies